Annotated Catalogue of Edwin’s Filmworks (2002-2025) - Atikah Az Zahra; Andreas Sudjud Dartanto; Dian Ajeng Kirana (Institut Seni Indonesia Yogyakarta, 2026)
As an effort to preserve artworks, archiving plays a crucial role in recording evidence of an artwork's existence and all its supporting data. Therefore, an annotated catalogue could be an option for archiving works in an organized manner and be presented with supported information. In context of the film industry, a director plays the role of an artist, as they determine the creative vision of a film. In Indonesia, many directors have colored the world of cinema with works that have received international recognition, one of which is Edwin. He is an Indonesian film director, screenwriter, editor, and producer whose filmworks are known for its poetic and surrealist perception. The method for creating this annotated catalogue consists of data collection, data processing, and data presentation using an aesthetic approach with the creation process of pre-production, production, and post-production. The presentation of information in this annotated catalogue includes visual and textual archives of Edwin's film works, divided into short films, feature films, documentaries, and omnibus films, and is arranged in chronological order. The catalogue dimension is B5 paper size 17.6 cm x 25 cm with the total number of filmworks presented are 41 works which includes 25 short films, 7 feature films, 4 documentary films, and 5 omnibus films.